Transradial versus Transfemoral Approach for Primary Percutaneous Coronary Intervention Single Centre Experience over a Period of Two Years - Haq, Maksumul; Kabir, CM Shaheen; Haq, M Mahshid; Khan, Saidur Rahman; Chowdhury, Mashhud Zia; Nasrin, Sahela; Karim, Md Rezaul (University Heart Journal, 2017)
Background: Primary percutaneous coronary intervention (PPCI) is preferred over thrombolysis due to its better outcome both in terms of morbidity and mortality. Transradial (TR) PPCI is favored over transfemoral (TF) approach due to several advantages including survival benefit. Only concern of TR PPCI is a possible delay in door-to-balloon (D2B) time which is an important parameter for a better outcome. This retrospective analysis compared various outcome variables including D2B time between TF versus TR groups in order to decide which approach provides better outcome over the other. Methods: This study was conducted at Ibrahim Cardiac Hospital & Research Institute (ICHRI) on retrospective data collected over a period of 2 years between January 2013 to December 2014. Patients with ST-segment elevation myocardial infarction (STEMI) attending at Emergency Department of ICHRI within 12 hours of chest pain and were sent for PPCI were consecutively included in the study based on predefined enrollment criteria. Demographic, angiographic & angioplasty variables, D2B time, duration of hospital stay and mortality were compared between TF versus TR groups. Results: Of the 92 patients included in the study, 47(51.1%) patients underwent PPCI through TF access whereas 45(48.9%) patients through TR access. There was an increasing trend of performing PPCI via TR access in 2014 compared to 2013 (64.4% vs. 35.6%). There was no significant difference between the study groups in terms of age and sex. Baseline angiographic & angioplasty variables were almost similar between the groups. The mean D2B time was significantly shorter in TR group than that in TF group (79.0 ± 34.6 vs. 90.3 ± 37.7 min, p=0.021). One patient in each group died from ventilator associated pneumonia after PPCI. Conclusion: Our single center retrospective analysis showed a statistically significant decrease in the door to balloon time with TR PCI, which makes it an attractive option for PPCI in STEMI. University Heart Journal Vol. 11, No. 2, July 2015; 56-62